The Development of the CSR Concept and Theories - Księżak, Paulina; Szkolmowska, Joanna (Journal of Corporate Responsibility and Leadership, 2019)
Purpose: The aim of this paper is to study the origins and development of the concept and discuss the evolution of the views on the matter of CSR. Design/methodology/approach: The narrative literature review methodology is applied to achieve the aim of the study. The paper is divided into two main sections. In the first one, the development of the CSR concept is presented. In the second one, the variety of theories related to the issue of social responsibility of business organisations is discussed. Findings: The papers points out relations between development of the CSR concept and evolved theories referring to the matter of CSR. Research and practical limitations/implications: The article is theoretical and may be subject to further research. However, analysing the data basing only on the literature review may appear as the limitation of the study. Originality/value: A major concern of the article is the development of the CSR concept. The paper elaborates it in relation to the evolved theories on the matter of CSR. The value that it contains plays a significant role, especially in the occurrence of development of CSR policies in companies around the world. Paper type: literature review.